2019
DOI: 10.1111/ppl.12863
|View full text |Cite
|
Sign up to set email alerts
|

LSD1‐, EDS1‐ and PAD4‐dependent conditional correlation among salicylic acid, hydrogen peroxide, water use efficiency and seed yield in Arabidopsis thaliana

Abstract: In Arabidopsis thaliana, LESION SIMULATING DISEASE 1 (LSD1), ENHANCED DISEASE SUSCEPTIBILITY 1 (EDS1) and PHYTOALEXIN DEFICIENT 4 (PAD4) proteins are regulators of cell death (CD) in response to abiotic and biotic stresses. Hormones, such as salicylic acid (SA), and reactive oxygen species, such as hydrogen peroxide (H2O2), are key signaling molecules involved in plant CD. The proposed mathematical models presented in this study suggest that LSD1, EDS1 and PAD4 together with SA and H2O2 are involved in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 90 publications
2
56
0
1
Order By: Relevance
“…The RCD phenotype is induced by a superoxide anion (O 2 − ) and H 2 O 2 , which are excessively produced in an lsd1 mutant [37,38,39,40,41,42,43,44]. Hormones important for plant defense i.e., salicylic acid (SA) and ethylene (ET) are also over-accumulated in lsd1 [35,40,42,44,45]. It was found that in the NahG/ lsd1 plants that are unable to accumulate SA because of the NahG bacterial gene, encoding salicylate hydroxylase that converts SA to catechol, cell death was suppressed [46].…”
Section: Lsd1 Eds1 and Pad4 Play A Crucial Role In The Response mentioning
confidence: 99%
See 4 more Smart Citations
“…The RCD phenotype is induced by a superoxide anion (O 2 − ) and H 2 O 2 , which are excessively produced in an lsd1 mutant [37,38,39,40,41,42,43,44]. Hormones important for plant defense i.e., salicylic acid (SA) and ethylene (ET) are also over-accumulated in lsd1 [35,40,42,44,45]. It was found that in the NahG/ lsd1 plants that are unable to accumulate SA because of the NahG bacterial gene, encoding salicylate hydroxylase that converts SA to catechol, cell death was suppressed [46].…”
Section: Lsd1 Eds1 and Pad4 Play A Crucial Role In The Response mentioning
confidence: 99%
“…LSD1 plays an important role in the response and acclimation of plants to a broad range of stresses such as drought [35,48], UV-C radiation [44,46], cold stress [49], excess light [41], root hypoxia [42] and pathogens [43]. Interestingly, the lsd1 phenotype shows conditional dependence on environmental conditions, and the morphology and seed yield of the mutant does not differ from the wild type when plants are grown under field conditions [35,45]. LSD1 acts as a negative regulator of EDS1 and PAD4 [43,44,45,50,51] in PCD, and double mutants eds1/lsd1 and pad4/lsd1 demonstrate a reverted RCD phenotype, even under stress conditions [44,45].…”
Section: Lsd1 Eds1 and Pad4 Play A Crucial Role In The Response mentioning
confidence: 99%
See 3 more Smart Citations